PERANCANGAN SISTEM INFORMASI AKUNTANSI UNTUK SISTEM PIUTANG - Kusumawati, Dara (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2014)
Now a days many sales transactions are done on credit, so this raises the receivables. The number of mutations receivables transaction requires the owner to improve the management of accounts receivable so that mutations can be generated reports of rapid and accurate accounts. It is necessary for the design of accounting information systems for accounts receivable system. Information system design research methodology used is receivable accounting system starters, system analysis, system design, system implementation and system testing. Accounting Information Systems for receivable system will do the recording onset and reduced accounts receivable and will produce basic information such as accounts receivable, accounts receivable cards each debtor, and Statement of accounts receivable aging analysis of receivables.